Digital Transformation and the Impact of Business Law in Global Economic Regulation Politics - Ryan Rudyarta; Fikri Ardiyansyah; Moh Ibrohim; Bella Nanda Ardhya (International Journal of Humanities and Social Sciences Reviews, 2025)
Digital transformation is reshaping the way economic value is created, exchanged, and governed across borders. This study aims to analyze how digital transformation redefines the paradigm of business law in the era of globalization, as well as the interaction between business law and global regulatory politics in responding to the challenges of the digital economy. A normative legal approach is employed, grounded in the analysis of digital business law regulations within the global political-economic system. Data is collected through literature review of statutory frameworks, international policy instruments, and scholarly works. The findings reveal that digital transformation not only changes how transactions are conducted, but also reconfigures the locus of economic power through the control of data, algorithms, and digital platform infrastructure. Consequently, the legal paradigm shifts from merely regulating market actors’ behavior to designing a digital justice architecture that emphasizes accountability, algorithmic transparency, interoperability, and contestability. At the global level, the interaction between business law and digital regulatory politics reflects ongoing tensions between market openness and data sovereignty producing regulatory pluralism while simultaneously encouraging convergence toward principles of fair, adaptive, and responsive digital governance. This study concludes that business law in the digital era must serve not only as a regulatoryinstrument governing transactions, but as an architect of the global economic order one that safeguards innovative growth without compromising market fairness and fundamental rights, while enabling the strengthening of adaptive national regulatory frameworks aligned with evolving global dynamics.